2022
DOI: 10.2147/ndt.s350588
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Hemoglobin-to-Red Cell Distribution Width Ratio and All-Cause Mortality in Ischemic Stroke Patients with Atrial Fibrillation: An Analysis from the MIMIC-IV Database

Abstract: Aim To investigate the association between the hemoglobin-to-red cell distribution width (RDW) ratio (HRR) and all-cause mortality in ischemic stroke patients with atrial fibrillation (AF). Design This study was a retrospective cohort analysis. In total, 1018 ischemic stroke patients with AF were enrolled using the Medical Information Mart for Intensive Care database, (MIMIC)-IV. The patients were divided into four groups according to the HRR values. The primary outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It is widely employed in the early differential diagnosis of anemia [ 6 ]. Recent research has revealed a strong correlation between a high RDW and the prognosis of a variety of serious diseases, including cancer [ 7 ], cardiovascular diseases [ 8 ], ischemic stroke [ 9 ], and acute respiratory distress syndrome (ARDS) [ 10 ]. RA is the ratio of RDW to albumin, and a study showed that the predictive value of RA in stroke patients is even greater than that of RDW [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely employed in the early differential diagnosis of anemia [ 6 ]. Recent research has revealed a strong correlation between a high RDW and the prognosis of a variety of serious diseases, including cancer [ 7 ], cardiovascular diseases [ 8 ], ischemic stroke [ 9 ], and acute respiratory distress syndrome (ARDS) [ 10 ]. RA is the ratio of RDW to albumin, and a study showed that the predictive value of RA in stroke patients is even greater than that of RDW [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A series of previous studies have demonstrated that a low level of HRR was associated with poor outcomes among multiple malignant diseases (25,33,(38)(39)(40)(41). In recent years, there was mounting evidence that a lower level of HRR was strongly associated with significantly worse outcomes in many critically ill patients, such as coronary heart disease (28), sepsis (29), ischemic stroke (30), and so on. One study with 6,046 participants found that a lower HRR (HRR<10.25) in patients with percutaneous coronary atherosclerotic heart disease was associated with a 1.47-fold increased risk of long-term allcause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have shown that HRR was associated with inflammation (25)(26)(27). In recent years, more and more evidence has shown that low level of HRR was closely related to significantly deteriorating prognosis in many critically ill patients, such as coronary heart disease, sepsis, and ischemic stroke (28)(29)(30). However, the relationship between HRR and mortality in patients with non-traumatic SAH is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that HRR is a new prognostic indicator in critically ill patients with malignant diseases. For example, Qin et al explored the nonlinear relationship between all-cause mortality and HRR value in patients with ischemic stroke [ 27 ], and Rahamim et al found that HRR was an important prognostic tool for predicting mortality in heart failure and the hospitalization of patients with cardiovascular disease [ 9 ]. Chi et al found that low HRR were associated with a dual risk of disease progression or cancer recurrence in patients and used them to predict poor prognosis in patients with cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%